A descriptive quantitative study of 7- and 8-year-old children's outdoor recreation, cold exposure and symptoms in winter in Northern Finland. Issue 1 (1st January 2017) - Rasi, Hanna; Kuivila, Heli; Pölkki, Tarja; Bloigu, Risto; Rintamäki, Hannu; Tourula, Marjo
ABSTRACT: Background : In Finland, children spend a lot of time outdoors in winter. Outdoor recreation in winter has a wide variety of effects on children's well-being. Although children are a subgroup that is vulnerable to cold exposure, remarkably little research has been done on the subject. Objective: The aim of this study was to describe children's outdoor recreation, cold exposure and symptoms in winter in Northern Finland. Design: This was a descriptive quantitative study. The participants consisted of 30 children aged 7–8 years who were living in the provinces of Lapland and Northern Ostrobothnia in Finland. Data were collected by using electronic data-logging thermometers fixed on children's outerwear for a month. The thermometers recorded the environmental temperature every five minutes and from that temperature data, we were able to discern the exact amount and duration of children's outdoor recreation. In addition, information on the children's cold symptoms was collected with structured daily entries. Results: Cold weather was not an obstacle to children's outdoor activities in Finland. However, the duration of outdoor recreation shortened when the outdoor air temperature decreased. There were no significant differences between boys and girls in terms of time spent outdoors. Remarkably, every child reported symptoms associated with cold. Almost half of the children reported experiencing respiratory symptoms and some children also experienced cold pain and numbness. Conclusions: The results of this study illustrate the many and varied effects that cold exposure can have on children's health and well-being. In order to prevent negative health effects of cold exposure on children, structured prevention strategies are needed: therefore, children's exposure to cold should be studied more. Future research should also bring out more the positive health effects of outdoor recreation on children's growth and development.​​​​